Implementation of Standard Operating Procedures of Food and Beverage Service at Infinity8 Bali Hotel - Ni Putu Sri Devi Wahyuniati; I Gusti Agung Bagus Mataram; Ni Luh Eka Armoni; I Ketut Suja (International Journal of Travel, Hospitality and Events, 2023)
Purpose: This study aims to determine the implementation of standard operating procedures applied by food and beverage service employees and the managements to improve food and beverage service. Research methods: This study uses a qualitative descriptive analysis technique, which systematically describes the data obtained during the study starting from interviews, observations, questionnaires, literature studies, and quantitative descriptive analysis using a 5-level Likert scale. Data were obtained by distributing questionnaires on the implementation of standard operating procedure of food and beverage service to 9 respondents in the food and beverage service department. Results and discussion: From 13 standard operating procedures there are 11 standard operating procedures that have been implemented optimally, and 2 of standard operating procedures which is not maximum implementated yet such as selling by recommendation with a value of 3.81 and serving food and beverage with a value 4.19, as well as several points in standard operating procedures for seat the guest and menu presentation with a value of below 4.11. Implication: Conducting training, improving and maintaining the application of standard operating procedures, improving supervision and communication, and conducting evaluations to improve the services provided to guests need to do better. Keywords: implementation, standard operating procedures, food and beverage service.